Case Report: Disseminated primary pulmonary carcinoma presenting as a chronic enteropathy in a dog - Bandara, Yuvani; Shropshire, Sarah B.; Hughes, Kelly; Harris, Adam; Burton, Jenna Hart (Frontiers in Veterinary Science, 2026)
A 10-year-old, male castrated, mixed-breed dog presented with a four-month history of enteropathy unresponsive to standard treatment. Initial bloodwork ruled out non-gastrointestinal illness and abdominal ultrasound revealed stratified segmental small intestinal muscularis thickening. Gastrointestinal endoscopy and biopsy identified duodenal carcinoma with lymphatic infiltration. Due to the absence of an identified gross lesion, nascent primary duodenal carcinoma was suspected. The dog presented 29 days later for acute worsening of signs, development of neoplastic peritoneal effusion, and protein-losing enteropathy. Thoracic radiographs identified pulmonary nodules consistent with carcinoma on cytology. Humane euthanasia was elected 2 days later with necropsy identifying disseminated neoplastic emboli and marked lipogranulomatous lymphangitis. Strong positive nuclear labelling for thyroid transcription factor-1 of the pulmonary neoplasm and neoplastic cells within the small intestinal lymphatics of the original biopsy were consistent with disseminated primary pulmonary carcinoma (PPC). This is the first report describing disseminated PPC presenting primarily with gastrointestinal signs.